High-dose therapy with BEAC conditioning compared to BEAM conditioning prior to autologous stem cell transplantation for non-Hodgkin lymphoma: no differences in toxicity or outcome. A matched-control study of the EBMT-Lymphoma Working Party. (December 2018) - Robinson, Stephen; Boumendil, Ariane; Finel, Herve; Dreger, Peter; Sureda, Anna; Hermine, Olivier; Montoto, Silvia
Abstract A recent shortage of melphalan has prompted the use of alternatives to BEAM (BCNU, Etoposide, Cytarabine, Melphalan) conditioning for autologous stem cell transplantion (ASCT). The BEAC (BCNU, Etoposide, Cytarabine, Cyclophosphamide) regimen has been employed as a conditioning regimen in lymphoma patients. However, there have been recent concerns about the toxicity of BEAC. We conducted a retrospective analysis of the EBMT database comparing the outcome of patients conditioned using BEAC with a matched cohort of patients conditioned with BEAM. In the BEAC cohort (n = 383), 25 patients died from non-relapse mortality (NRM) events (32% owing to MOF or cardiac toxicity). In the BEAM cohort (n = 766) there were 34 NRM events (23% owing to MOF or cardiac toxicity). The 1-year cumulative incidence of NRM was 4% in the BEAC cohort and 3% in the BEAM group (p = ns). The 2-year relapse/progression rate was 32% with BEAC and 33% with BEAM (p = ns). At 2 years the progression-free survival (PFS) and overall survival (OS) were 63% and 78% for BEAC and 63% and 77% for BEAM-conditioned patients (p = ns for PFS and OS). The toxicity observed with BEAC conditioning as measured by NRM was similar to that seen with BEAM. The outcomes following BEAC were similar to those seen with BEAM, suggesting that BEAC is a safe conditioning regimen.